Technology transfer success: An investigation of contributory factors - Wickramasinghe, Vathsala; Madhusanka, Niroshan (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2024)
Abstract. The purpose of the study was to investigate factors that contribute to the success of technology transfers. The specific objectives were to investigate 1) technological capabilities acquired by recipient firms through the technology transfer at the project level, 2) contributory factors that influence technology transfer, and 3) whether technological capabilities acquired by recipient firms are affected by these contributory factors. The study was conducted in Sri Lanka. The study developed a set of success factors and performance indicators to assess technological capabilities acquired by technology recipient firms. The study found two main types of technological capabilities gained by recipient firms through the technology transfer - “converting and acquiring capability” and “vending, modifying and generating capability”. Further, the study found five contributing factors for technology transfer - process management, intended use of technology, transfer components, technology needs analysis, and IP protection and licensing. It is also found that all five contributing factors significantly positively predict both types of technological capabilities gained by recipient firms through technology transfer. The findings of the study presented in this paper make valuable contributions to the existing literature on technology management and technology transfer. Keywords: Asia, developing countries, international technology transfer, technology transfer, technology capabilities